2009
DOI: 10.1097/pai.0b013e31819640f9
|View full text |Cite
|
Sign up to set email alerts
|

Role of HERV-W Syncytin-1 in Placentation and Maintenance of Human Pregnancy

Abstract: Over half of human genome contains retroelements, including retrotransposons, retroviruses, and other elements. Human endogenous retroviruses (HERVs) comprise about 8% of human genome. The products of 2 of 16 identified genes of HERV-W seem to play a pivotal role in the placentation. These 2 genes are HERV-W env glycoprotein (syncytin-1) and HERV-FRD env glycoprotein (syncytin-2). It has been shown previously that syncytin-1 mediates cell-cell fusions of cytotrophoblasts into syncytiotrophoblasts. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…However, after eliminate the contribution of cell proliferation, adjusted by PCNA , an indicator of cell proliferation, there was no significant difference between discordant twins. We speculated that the alteration of HERVWE1 transcript level was related to the cell proliferation, since it has been found that one of HERVWE1 's important function is proliferation [3], [28]. Previous study had verified that the HERVWE1 expression was synchronous with the PCNA expression in endometrial carcinoma tissue [28].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, after eliminate the contribution of cell proliferation, adjusted by PCNA , an indicator of cell proliferation, there was no significant difference between discordant twins. We speculated that the alteration of HERVWE1 transcript level was related to the cell proliferation, since it has been found that one of HERVWE1 's important function is proliferation [3], [28]. Previous study had verified that the HERVWE1 expression was synchronous with the PCNA expression in endometrial carcinoma tissue [28].…”
Section: Discussionmentioning
confidence: 98%
“…Over the past few years, researchers have found that human endogenous retroviral family W, Env (C7), member 1 ( HERVWE1 ), which is highly expressed in placental tissue, is the critical gene that regulates the action and preservation of the syncytium [1], [2]. The protein product of HERVWE1 is syncytin-1, which mediates special functions in the placenta, including fusion, proliferation, anti-apoptosis, and immune suppression [3], [4]. The fusion function of syncytin-1 promotes the merging of cytotrophoblast cells to form the syncytiotrophoblast cell, which secretes several endocrine hormones that promote fetal growth, such as human chorionic gonadotrophin (HCG) and human chorionic somatomammotropin (HCS).…”
Section: Introductionmentioning
confidence: 99%
“…Steroid hormones and inflammation are known risk factors for OA [5863]. Interestingly, these conditions can also induce activation of HERV [64–67]. A drawback of our study is that relatively few non-OA patients were examined and their average age was significantly younger than the OA patients (range 25–45 years versus 30–82 years).…”
Section: Discussionmentioning
confidence: 99%
“…genes are known to have been exapted in the placenta, for example the HERV-W Env gene Syncytin has acquired a functional role in placental syncytiotrophoblast formation (Frierson et al, 2003;Hassan and Ho 2008;Noorali et al, 2009;Prudhomme et al, 2004). In several cases (EDNRB, PTN, CYP19A1, and PAPPA2) orthologs in other mammals are also expressed in the placenta, but not due to retroviral insertion (Rawn and Cross 2008).…”
Section: Placental Specificity Of Ltrsmentioning
confidence: 97%